Design, Construction and Testing of a Low Cost Ground Sta-tion for CubeSat with IoT-LoRa Technology - Flores Cadena, Gary Fernando (2024)
This research article presents the design and construction of a low-cost ground station, consisting of a Yagi antenna, Low Noise Amplifier (LNA), and a LoRa receiver node, enabling the reception of CubeSat signals utilizing LoRa technology. The design incorporates general antenna and electronic amplifier design concepts and was validated through laboratory tests assessing elec-trical characteristics, signal radiation, and frequency response. This setup successfully received telemetry data from LoRa-based CubeSat satellites.